Annual review of comparative and international education 2017. Vol. 34 - Wiseman, Alexander W., 1968- (Emerald Publishing Limited, 2018)
This year's Annual Review of Comparative and International Education surveys the field from several globally representative perspectives. Contributors include scholars, policymakers and development consultants and cover comparative and international education trends and issues unique to Africa, Asia, Europe, North America, Oceania, and South America. This volume is representative of a wide range of recent trends and important concerns in the CIE community worldwide and within particular regions or specific communities. Additionally, the Annual Review celebrates its fifth year of continuous publication this year, which highlights the ongoing interest in and importance of reflective practice and the professionalization of comparative and international education.
Includes index.
Print version record
Keywords: Comparative education; International education; Education. -- Comparative; Educational strategies & policy